Simple steps to data encryption : a practical guide to secure computing - Loshin, Peter (Syngress, 2013)
Provides simple descriptions of actual data threat scenarios alongside step-by-step instructions for securing it. Demonstrates how to use open source, time-proven and peer-reviewed cryptographic software, and gives easy to follow tips for safer computing, as well as unbiased and platform-independent coverage of encryption tools and techniques.